Subclinical and clinical contrast-induced acute kidney injury: data from a novel blood marker for determining the risk of developing contrast-induced nephropathy (ENCINO), a prospective study. (18th December 2014) - Akrawinthawong, Krittapoom; Ricci, Jason; Cannon, Louis; Dixon, Simon; Kupfer, Kenneth; Stivers, David; Alexander, Patrick; David, Shukri; McCullough, Peter A.
Abstract: Objective : Neutrophil gelatinase-associated lipocalin (NGAL) is produced in response to tubular injury. Contrast-induced acute kidney injury (CI-AKI) is associated with adverse outcomes in chronic kidney disease (CKD) patients. We sought to characterize blood NGAL level and the degree of kidney injury in CKD patients who underwent coronary angiography. Methods : This study was a prospective, blinded assessment of blood samples obtained from patients with estimated glomerular filtration rates (eGFRs) between 15 and 90 mL/min/1.73 m 2 undergoing elective coronary angiography with iodinated contrast. Blood NGAL and serum creatinine were measured at baseline, 1, 2, 4, 6, 12, 24 and 48 h after contrast administration. Results : A total of 63 subjects with a mean eGFR of 48.17 ± 16.45 mL/min/1.73 m 2 were enrolled. There was a graded increase in baseline NGAL levels across worsening stages of CKD ( p  = 0.0001). Post-procedure NGAL increased from baseline in each stage of CKD. Eight (12.7%) patients were diagnosed with CI-AKI by diagnostic criteria of 2012 KDIGO definition of CI-AKI, and seven (11.1%) patients developed subclinical CI-AKI defined by a twofold or greater rise in NGAL. There was no relationship between baseline eGFR and diabetes on the composite outcome of subclinical and clinical CI-AKI. Conclusions : Baseline and post-procedure NGAL are progressively elevated according to the baseline stage of CKD. Using a twofold rise in NGAL, 46.7% of composite CI-AKI is detected and complements the 53.3% of cases identified using KDIGO criteria. Traditional risk predictors were not independently associated with this composite outcome.